(2x+3)/(x-4) - (2x-8)/(2x+1) =1

(2x+3) (2x+1) = 4x^2 + 8x + 3

(2x-8) (x-4) = 2x^2 - 16x - 32

(4x^2+8x+3) - (2x^2-16x-32) = 1

2x^2 - 8x - 29 = 1

2x^2 - 8x - 30 = 0

x^2 - 4x - 15 = 0

Using the quadratic formula;

x = 6.36 or x= -2.36 to 2dp

Answered by Masie A. Maths tutor

1405 Views

See similar Maths 13 Plus tutors

Related Maths 13 Plus answers

All answers ▸

The following sequence reads: 8, 5, 2, -1. What are the 4th and 50th terms of this sequence?


How do I find the area of a circle C with diameter 14cm?


Simplify the following expression fully: 8x + y - 6y − 5x


Factorise the following equation fully: 2x^2+12x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences